2018
DOI: 10.1155/2018/4831593
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fractioning on Antibacterial Activity of Enantia chlorantha Oliver (Annonaceae) Methanol Extract and Mode of Action

Abstract: Infectious diseases caused by bacteria constitute the main cause of morbidity and mortality throughout the world and mainly in developing countries. In this work, the influence of fractioning and the mode of action of stem barks methanol extract of Enantia chlorantha were investigated. The aim was to optimize the antibacterial activity of the methanol extract. The extract was prepared by maceration of barks powder in methanol. Fractioning was done using increasing solvents polarity. Standard phytochemical meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
1
4
0
2
Order By: Relevance
“…In addition, these active compounds are commonly targeted at multiple sites rather than one specific site of antibacterial action [27,28]. For example, Ebelle et al [29] reported that the methanolic extract of Enantia chlorantha had several modes of antibacterial action including the extension of the bacterial latency period, the deactivation of H+ -ATPases activity in cell membrane, the loss of the salt tolerance of the S. aureus, and inhibition of the biofilm formation. Since TCMP extracts contain diverse chemical substances, they probably influence the bacteria cell constituents or molecular targets by various mechanisms.…”
Section: Screening Of Antibacterial Tcmp Extracts Against Antibiotic-mentioning
confidence: 99%
“…In addition, these active compounds are commonly targeted at multiple sites rather than one specific site of antibacterial action [27,28]. For example, Ebelle et al [29] reported that the methanolic extract of Enantia chlorantha had several modes of antibacterial action including the extension of the bacterial latency period, the deactivation of H+ -ATPases activity in cell membrane, the loss of the salt tolerance of the S. aureus, and inhibition of the biofilm formation. Since TCMP extracts contain diverse chemical substances, they probably influence the bacteria cell constituents or molecular targets by various mechanisms.…”
Section: Screening Of Antibacterial Tcmp Extracts Against Antibiotic-mentioning
confidence: 99%
“…Though the exact mechanism of anti-inflammatory action is unknown, the percentage inhibition of total oedema over the 6 h-period of observation suggests that the extracts may have inhibited the release or action of one or more of these inflammatory mediators. From the results, the whole extract of A. genipiflora (AG) had a higher anti-inflammatory effect than its MeOH (AGM), EtOAc (AGEt), and petroleum ether (AGPE) fractions implying a possible synergistic effect of constituents in the whole extract that were lost during fractionation ( Ebelle-Etame et al., 2018 ). Among the fractions, AGEt and AGM showed similar anti-inflammatory activity better than AGPE.…”
Section: Discussionmentioning
confidence: 99%
“…Solvents can also affect the antimicrobial activity of herbal plants. 22,23 The chemical ingredients in gambier that are most widely used are catechins and tannins. Catechins are oligomeric procyanidin (OPC) tannin compounds classified as flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…This result is influenced by the content of bioactive compounds found in each solvent. 23 The polarity of the solvent plays an important role in increasing the solubility of the bioactive compound. 10,11,24,25 The difference in the polarity of the solvent determines the difference in the type and composition of the phytochemical compounds.…”
Section: Discussionmentioning
confidence: 99%